Successful pregnancy outcome in Eisenmenger Syndrome in pregnancy: a case report - Roslan, Siti Ruziana; Norawi, Adienuar Ahmad; Abdul Hadi, Azwanis (Science Forecast Publications, 2021)
We present an antenatal case with established Eisenmenger Syndrome (ES) who refused termination of pregnancy. Her pregnancy continued until an emergency caesarean section for IUGR at 31 weeks gestation. This case report illustrates an example of a good health care model especially for primary care level that led to a successful pregnancy outcome in a high-risk patient.